Recent Trends in Green Chemistry: A Bibliometric Analysis of Materials and Innovations: Tren Terkini dalam Green Chemistry : Analisis Bibliometrik Materi dan Inovasi - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (IAIN Sorong, 2024)
This descriptive study conducted a bibliometric analysis to describe research trends in Green Chemistry literature. The secondary data used were 200 scientific publications on Green Chemistry published between 2020 and 2024. The analysis results show that Green Chemistry has a strong interest and a significant number of publications in the world of scientific research. The high average citations per researcher indicate the relevance and significance of the research in the scientific community as well as its relevance to responding to complex environmental and industrial challenges. The high average number of publications per researcher shows the great interest and continuous contribution of researchers in expanding knowledge about green chemistry. This emphasizes the importance of working together, communicating, and committing to sustainable research to address environmental and business issues. Some evidence of the impact and relevance of research in the scientific literature includes high h and g indices and significant average citations per year. Articles on green chemistry continue to attract the attention of the scientific community and make significant contributions to the advancement of our knowledge and understanding of the field. Recent trends show significant interest in elements such as process, leafe, and cooper, indicating the direction of the latest research and developments in green chemistry.